Effect of feed restriction on compensatory growth of Arsi (Bos indicus) bulls - Tolla, N.; Mirkena, T.; Yimegnuhal, A. (Elsevier, 2003)
A study was conducted to evaluate the efficiency of compensatory feeding. Twenty-five Arsi bulls (32±4 months) were blocked by weight and randomly allocated to the following feed restriction treatments: ad libitum feeding for the entire period (control), maintenance feeding level (maintenance), 15% body weight loss (-15%), 20% body weight loss (-20%) and 25% body weight loss (-25%). A 91-day period of feed restriction was followed by a 105-day re-alimentation period. No treatment effects was observed on average daily gain (ADG) or feed conversion efficiency (FCE) during the compensatory period, both between control and maintenance feeding levels, and within the restricted treatment groups. Recovery index differed (P<0.01) both between the control and maintenance groups as well as within restricted treatments. Compensation was not complete, perhaps due to the low energy diet or insufficient time for compensation. No treatment effects on any carcass traits were observed between the ad libitum (control) and maintenance level feeding except ingesta (P<0.01) and among (P<0.05) restricted groups (Table 4). Effects of feeding levels linearly decreased slaughter weight (Wt2) and ingesta weight (P<0.05), as well as carcass and lean meat yield (P<0.01). Proportions of lean meat, fat and bone to total carcass and slaughter weight differed (P>0.05) between control and maintenance groups as well as among restricted treatments. Although statistically not significant, compensatory gains, FCE, and lean meat yield for treatments -15, -20 and -25% had increasing tendencies with increasing levels of feed restriction. Therefore, Arsi bulls need longer than 105 days of compensatory feeding for complete recovery of LW losses caused by different levels of restriction in a period of 91 days. The appropriate time of feeding and change in the energy density of the diet by manipulating the roughage and concentrate ratios for complete compensation following different levels of retarded growth along with cost–benefit relationship requires further investigation.